2018
DOI: 10.3390/inorganics6040134
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo-Phenanthroline Ligands as a Convenient Modular Platform for the Preparation of Heteroleptic Cu(I) Photosensitizers

Abstract: The capture and storage of solar energy is a promising option to overcome current energy issues. To put such systems into practice, molecular photosensitizers should be based on abundant metals and possess a strong absorption capability for visible light. Therefore, a systematic series of four novel heteroleptic Cu(I) complexes of the type [(P^P)Cu(N^N)]+ (with P^P = xantphos and N^N = different diimine ligands) has been prepared. As an essential feature, these copper photosensitizers contain an imidazole moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Upon anodic scanning, two irreversible peaks appear for the four Cu­(I) 4 H -imidazolate complexes in DCM (0.50, 0.95 V ( Phe ); 0.40, 0.86 V ( Tol ); 0.46, 0.97 V ( Mes ), 0.59, >1 V ( COOEt ) vs Fc/Fc + ) and in ACN (0.61, 0.78 V ( Phe ); 0.57, 1.01 V ( Tol ); 0.52, 0.84 V ( Mes ), 0.93, 1.21 V ( COOEt ) vs Fc/Fc + ). These oxidation events are assigned to a Cu­(I)-centered oxidation ( E ox,1 ) as well as a xantphos oxidation ( E ox,2 ). ,, ,,,, The observed trend of the copper-based oxidation potentials of COOEt , Phe , Tol , and Mes in both DCM and ACN also reflects an increasing electron density on the copper center as a consequence of the N -aryl +I effect (Table and SI Figure S11).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Upon anodic scanning, two irreversible peaks appear for the four Cu­(I) 4 H -imidazolate complexes in DCM (0.50, 0.95 V ( Phe ); 0.40, 0.86 V ( Tol ); 0.46, 0.97 V ( Mes ), 0.59, >1 V ( COOEt ) vs Fc/Fc + ) and in ACN (0.61, 0.78 V ( Phe ); 0.57, 1.01 V ( Tol ); 0.52, 0.84 V ( Mes ), 0.93, 1.21 V ( COOEt ) vs Fc/Fc + ). These oxidation events are assigned to a Cu­(I)-centered oxidation ( E ox,1 ) as well as a xantphos oxidation ( E ox,2 ). ,, ,,,, The observed trend of the copper-based oxidation potentials of COOEt , Phe , Tol , and Mes in both DCM and ACN also reflects an increasing electron density on the copper center as a consequence of the N -aryl +I effect (Table and SI Figure S11).…”
Section: Resultsmentioning
confidence: 96%
“…One of the current greatest challenges in science and technology is the conversion of solar energy into chemical energy. Among the many contemporary concepts, artificial photosynthesis holds great promise. In artificial photosynthesis, photocatalysts are employed to produce fuels and chemicals by harvesting solar energy. In this context, transition-metal complexes are of interest as photosensitizers due to their versatile optical and electronic properties. , Especially noble-metal-free systems are currently investigated as molecular components in photocatalytic schemes to produce hydrogen from water. ,, To this end, the requirements for an ideal photosensitizer to capture sunlight and initiate a charge transfer cascade are: a broad and intense absorption in the visible region, reversible electrochemical behavior, high stability under reaction conditions, and a long-lived excited state. ,,,, Cu­(I) complexes meet these requirements and present an emerging class of molecular photosensitizers due to their straightforward and low-cost synthesis. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the TPSs are based on expensive transition metal complexes of [Pt­(II), Ir­(III), or Ru­(II) ] or bromo- or iodo-containing organic chromophores. , Many examples of TPSs have been reported to be based on 1,10-phenanthroline. Among these, it has been observed that substitutions at the 2- and 9-position of the phenanthroline-based ligands sterically restrict excited-state distortion, thereby lengthening the excited-state lifetime. Unfortunately, heavy metal based complexes present severe problems due to enhanced dark toxicity . Further, heavy atom free organic triplet photosensitizers are rather scarce, largely due to the low ISC efficiency of common organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Cu­(I) complexes, which can be photoactivated by visible light, are considered promising earth-abundant alternatives to commonly employed ruthenium, platinum, iridium, or rhodium complexes in light-driven processes, such as photosensitizers in artificial photosynthesis, photoredoxcatalysis, or dye-sensitized solar cells. Heteroleptic Cu­(I) complexes of the type [Cu­(I)­(N ∧ N)­(P ∧ P)] + (with P ∧ P as diphosphine and N ∧ N as a diimine ligand) exhibit strong absorption of ultraviolet light and moderate absorption in the visible spectrum, often alongside with long microsecond excited-state lifetimes . However, while the redox properties and excited-state lifetimes can be optimized by tuning the electronic structure of the ligands, ,,, the tuning of the light-harvesting ability toward broad absorption in the visible spectrum is challenging. ,, An exception to that are heteroleptic [Cu­(I)­(Xantphos)­(4 H -imidazolate)] complexes (cf. Figure ), reported by us. , They exhibit unusually broad and intense absorption bands that span the visible spectrum with extinction coefficients up to about 2 × 10 4 M –1 cm –1 .…”
Section: Introductionmentioning
confidence: 99%